STUDENT RESILIENCE AFTER PANDEMIC : LEARNING LOSS RECOVERY - Eem Munawaroh; Yuli Nurmalasari (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2021)
After approximately 2 years of being closed as a result of the Covid-19 pandemic, currently, schools around the world are starting to open even with limited meetings. Online learning as the best alternative learning mode during the pandemic has caused a learning loss effect on students so that students must be able to adapt and have resilience when returning to the school environment to recover learning loss. The purpose of this article is to review the latest literature on recovery learning loss, including the strategies that schools, teachers, and parents should develop in developing student resilience in adapting to school new normal. The results of the literature review of the latest sources regarding recovery learning loss, there are several strategies that can be developed, involve the school community in school opening plans, ensure school health and safety protocols, ensure the psychological well-being of students, identify students who most need help, and improve pedagogical practice and teacher training.